Microscopic evaluation of proliferative disorders in the gerbil female prostate: Evidence of aging and the influence of multiple pregnancies - Oliveira, Sergio M.; Santos, Fernanda C. A. [UNESP]; Corradi, Lara S. [UNESP]; Goes, Rejane M. [UNESP]; Vilamaior, Patricia S. L. [UNESP]; Taboga, Sebastiao R. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
The gerbil female prostate is located paraurethrally and has all the histological components of the male prostate, like secretor epithelium and fibromuscular stroma. This gland, like the prostate in males, is targeted by testosterone action, which promotes morphofunctional development. Furthermore, estrogens are required to maintain the male and female prostate and this gland presents both estrogen receptors (ER-alpha and ER-beta). In the present work the structural and morphometric-stereological and serological aspects, as well as the quantification of the incidence, multiplicity and percentage of acini affected by different lesions were analyzed. Animals were divided into four groups: five adult nuliparous (AN) gerbils; five adult multiparous (AM) gerbils; five senescent nulliparous (SN) gerbils; five senescent multiparous (SM) gerbils, and were weighed and sacrificed by CO(2) inhalation. The ventral prostate was dissected out, weighed and fixed to perform histological and morphometric-stereological analysis and quantification of prostate disorders. A high rate of lesions, mainly dysplasia, was identified in tissue from senescent multiparous and adult multiparous animals. Prostatitis was found mainly in SN animals, while dysplasia, hyperplasia, neoplasia, PIA and adenocarcinoma were common in SM ones. Although the proliferative lesion incidence was high in AN group, it was highest in the SM group. The hormonal events which occur due to the estrous cycle in female gerbils (after and before each pregnancy) may be responsible for the high number of lesions observed in our study and all the data presented herein lead us to assume that pregnancy promotes augmentations in both the incidence and the multiplicity of proliferative disorders in the gerbil female prostate since progesterone levels remain high during pregnancy. (C)011 Elsevier Ltd. All rights reserved.
Keywords: Female prostate; Aging; Pregnancy; Steroid hormone; Proliferative lesion; Progesterone